Karakteristik Pembakaran Dan Sifat Fisik Briket Ampas Empulur Sagu Untuk Berbagai Bentuk Dan Prosentase Perekat - Fretes, Evedore Fredo de; Wardana, I Nyoman Gede; Sasongko, Mega Nur (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2013)
Fossil fuel reserves are depleting to be anticipated by looking for alternative energy sources. Alternative energy that many developed and researched today is agricultural waste biomass fuel is formed into briquettes. In this research, briquettes are made from dregs the pith of sago in the four of form, namely : cylinders, blocks, cubes and prisms, with and without adhesive sago starch with the presentation of 5% and 10%.This research aimed to determine the effect form briquettes on the combustion rate and determine the physical properties of briquettes without carbonization process, with or without the addition of sago starch as an adhesive which include moisture content, ash content, volatile matter, fixed carbon and heating value.The results research that the form of briquettes affects the combustion rate where the fastest combustion speed was on briquettes form beams, cube and Prism. Percentage adhesive of sago starch affects the early combustion time where time is needed to ignite the briquettes greatest for percentage 10% and the lowest adhesive for briquettes without adhesives. Adhesive sago starch is also very influential on the moisture content, ash content, volatile substances, fixed carbon and heating value. Adhesive sago starch is also very influential on the moisture content, ash content, volatile matter, fixed carbon and heating value. The addition of adhesive sago starch lower heating value.Keywords: Briquettes, sago, Physical Properties, Combustion.